Perakitan Varietas Unggul Padi Beras Merah Aromatik Tekstur Nasi Pulen - Nugraha, Yudhistira; Rumanti, Indrastuti Apri; Sitaresmi, Trias; Rahmini, Rahmini; Rosa, Celvia; Handoko, Dody D; Sasmita, Priatna (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
Consumption of high nutritional is increasing; therefore, it is necessary to develop pigmented trice variety with high yield, good adaptability, and good grain quality favored by consumer such as soft texture. The development of aromatic rice variety includes crossbreeding, selection, yield trials, resistance test to pest and diseases, physico-chemical properties assay, analyzing of minerals contents and anthocyanin which were done consecutively during 2012 to 2016. The results showed that a promising line of BH39D-MR-11-1-1-6 revealed consistent grain yield in 16 multi-location yield trials both in the dry season and the wet season in average 6.78 t/ha dan 5.35 t/ha, respectively. The line demonstrated its yield potential of 10,67 t/ha, mid-resistance to biotype 1 of brown planthopper, resistance to pathotype III and mid-resistance to pathotype IV and VIII of bacterial leaf blight, and mid-resistance to four races of rice blast (race of 033, 073, 133 and 173). This line had relatively comparable iron content with the check variety of Inpari-5 Merawu but higher in zinc content compared to other lines tested. The dehulled rice was red and contains a high total phenolic compound amounting (5,743 mg AAE/100 g), and its texture was soft and fragrance. The BH39D-MR-11-1-1-6 has been released as new rice variety named as Inpari Arumba and had a great potential to become a national specialty rice choice.